2017
DOI: 10.1149/2.1211713jes
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Performance of Annealed Ni–P/(Etched Si) Negative Electrodes for Lithium–Ion Batteries

Abstract: The electrochemical performance of variously treated NiP coated Si (Ni-P/Si) negative electrodes for lithium-ion batteries was investigated. X-ray diffraction analysis revealed the formation of nickel silicide (NiSi and NiSi2) after annealing, which improved the adhesion between the NiP coating layer and Si particles. Spotty NiP particles did not aggregate on an etched Si surface due to an anchor effect, even after annealing, whereas the particles aggregated on an untreated Si surface. An annealed Ni-P/(etched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Many studies have addressed the above issues, by producing composite electrodes with improved mechanical properties, , increasing the electrical conductivity of Si by coating it with conductive materials, constructing nanostructured Si materials that accommodate volume expansion, and doping Si with impurities, including phosphorus (P) and boron, to lower its electrical resistivity and/or alter its properties, such as its phase transition, crystallinity, and morphology. Electrolytes also improve the performance and safety of rechargeable batteries. An increment in the energy density leads to a probability of burning. Hence, nonflammable electrolytes can improve the safety of rechargeable batteries.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have addressed the above issues, by producing composite electrodes with improved mechanical properties, , increasing the electrical conductivity of Si by coating it with conductive materials, constructing nanostructured Si materials that accommodate volume expansion, and doping Si with impurities, including phosphorus (P) and boron, to lower its electrical resistivity and/or alter its properties, such as its phase transition, crystallinity, and morphology. Electrolytes also improve the performance and safety of rechargeable batteries. An increment in the energy density leads to a probability of burning. Hence, nonflammable electrolytes can improve the safety of rechargeable batteries.…”
Section: Introductionmentioning
confidence: 99%
“…Film cracking with cycling may also be countered by increasing the electrical conductivity of Si as this can permit more uniform surface lithiation and minimize stress gradients. , A number of studies have investigated the role of dopants in Si in mitigating film fragmentation on cycling. Most reports have focused on crystalline Si (c-Si) due to its ability to be more readily modeled by using density functional theory (DFT) approaches. Long et al reported that the Li insertion potential shifts to lower voltages for P-doped and higher potential for B-doped (100) and (111) Si compared to intrinsic Si due to the positive (less favorable) insertion energy for the P-doped c-Si and negative insertion energy for B-doped Si .…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that Si-based electrodes offer greater lithiation/delithiation properties in some ionic-liquid electrolytes compared to that in conventional organicliquid electrolytes in addition to the safety. 8,[41][42][43][44][45][46][47] We have investigated the effect of cation structure of N-methyl-N-propylpyrrolidinium bis(trifluoromethanesulfonyl)amide (TFSA)-based ionicliquid electrolyte on the electrochemical performance of Si-based electrodes. 48 1-((2-methoxyethoxy)methyl)-1-methylpiperidinium (PP1MEM) cation played a role reducing the interaction between Li ion and TFSA anions, and Li + transfer at the electrode-Electrochemistry electrolyte interface in PP1MEM-TFSA was remarkably improved compared with that in 1-hexyl-1-methylpiperidinium (PP16)-TFSA; the introduction of ether functional group into cation is valid to enhance the electrode property.…”
Section: Introductionmentioning
confidence: 99%
“…We used 1 mol dm ¹3 (M) lithium bis(fluorosulfonyl)amide (LiFSA) dissolved in N-methyl-Npropylpyrrolidinium bis(fluorosulfonyl)amide (Py13-FSA) or 1ethyl-3-methylimidazolium bis(fluorosulfonyl)amide (EMI-FSA) as the electrolytes because most Si-based electrodes exhibited a superior performance in them. 8,[41][42][43][44][45][46][47] We also discussed the reaction behavior of FeSi 2 /Si composite electrodes compared to that of Siand FeSi 2 -alone electrodes.…”
Section: Introductionmentioning
confidence: 99%